Toward the Discovery of Citation Cartels in Citation Networks - Fister, Iztok; Fister, Iztok; Perc, Matjaž (Frontiers in Physics, 2016)
In this perspective, our goal is to present and elucidate a thus far largely overlooked problem that is arising in scientific publishing, namely the identification and discovery of citation cartels in citation networks. Taking from the well-known definition of a community in the realm of network science, namely that people within a community share significantly more links with each other as they do outside of this community, we propose that citation cartels are defined as groups of authors that cite each other disproportionately more than they do other groups of authors that work on the same subject. Evidently, the identification of citation cartels is somewhat different, although similar to the identification of communities in networks. We systematically expose the problem, provide theoretical examples, and outline an algorithmic guide on how to approach the subject.